Emerging niosomal formulations for skin-targeted drug delivery: strategies, applications, and limitations - Nurizan, Alya Nur Batrisya; Baharom, Aisyah Mahnum; Mohamed Ibrahim, Nur Hasanah; Alias, Atie Adianie; Darnis, Deny Susanti; Haris, Muhammad Salahuddin; Khotib, Junaidi; Bakhtiar, M. Taher (Taylor and Francis Ltd., 2026)
Nanomaterials has garnered significant interest in drug delivery owing to their ability to enhance targeted delivery to diseased tissues while minimizing exposure to surrounding healthy cells. However, achieving both safety and efficient delivery in therapeutic delivery remains a persistent challenge in pharmaceutical science. Niosomes, which are self-assembled vesicular nanocarriers formed by hydrating nonionic surfactants with cholesterol or other stabilizers, have emerged as a promising platform. These nanocarriers offer versatility in drug delivery applications, ranging from topical administration to targeted therapies. Similar to liposomes, niosomes are capable of encapsulating both hydrophilic and hydrophobic compounds. Moreover, they offer advantages such as simpler preparation methods, lower production costs, and enhanced stability, thereby overcoming several limitations of liposomal systems. This review presents an in-depth synthesis in emerging niosomal formulations, emphasizing strategies, therapeutic applications and limitations for improved skin-targeted drug delivery. Additionally, it highlights the therapeutic potential of niosomal drug delivery systems while addressing the challenges that may hinder their clinical translation. Compared to other nanocarriers such as liposomes and ethosomes, emerging niosomal systems exhibit superior structural stability, scalability, and adaptability for skin-targeted therapy, representing a critical step toward translational dermatological applications.